Characterization of 0.5 at % nd doped YVO4 pumped by diode laser - Bidin, Noriah (American Institute of Physics, 2011)
The output of diode laser pumped 0.5 at % Nd doped vanadate YVO4 crystal bar was characterized. Diode laser has wavelength centered at 808 nm. The pump power was focused to localize the high power density of source at the crystal bar surface. The output of diode pumped vanadate crystal was detected by a spectrum analyzer. The output radiation is centered at 1064 nm with linewidth of 1.15 nm. The stimulated emission cross section was estimated to be 14.94×10-19cm2. The intensity of the fluorescent beam was measured by powermeter and permanently recorded by using CCD video camera. The beam spot is TEMoo mode with beam divergence of 0.4°with the absent of intracavity. The optical -to-optical slope efficiency is found to be as 4.8% with threshold power of 1404 mW.